1984
DOI: 10.1152/jappl.1984.56.6.1464
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia on ventilation during postnatal development in conscious kittens

Abstract: Effects of steady-state hypoxia (inspired O2 fraction = 0.11) on ventilation and breathing pattern were studied during postnatal development in unanesthetized kittens. Studies were done from 2 days to 8 mo of age, every week during the first month and every month thereafter. During the first 2 months, states of consciousness were determined. In the first month, minute ventilation (VE) was depressed in hypoxia compared with control values in air, whereas in the older kittens VE was increased in hypoxia, as in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 21 publications
6
18
0
Order By: Relevance
“…Existing data supports the notion that the 'biphasic' and 'sustained' VRs represent sequential stages in the postnatal development of hypoxaemic sensitivity (Brady & Ceruti, 1966;Rigatto et al 1975;Woodrum et al 1981;Haddad et al 1982;Laframboise et al 1983;Bonora et al 1984;Bureau et al 1984;Bureau et al 1985). Our data suggest that these two categories may, in fact, represent discrete responses to specific hypoxaemic waveforms, and that it should not be assumed that a transition in oxygen responsiveness has Ventilatory response of lambs to hypoxaemia J. Physiol.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Existing data supports the notion that the 'biphasic' and 'sustained' VRs represent sequential stages in the postnatal development of hypoxaemic sensitivity (Brady & Ceruti, 1966;Rigatto et al 1975;Woodrum et al 1981;Haddad et al 1982;Laframboise et al 1983;Bonora et al 1984;Bureau et al 1984;Bureau et al 1985). Our data suggest that these two categories may, in fact, represent discrete responses to specific hypoxaemic waveforms, and that it should not be assumed that a transition in oxygen responsiveness has Ventilatory response of lambs to hypoxaemia J. Physiol.…”
Section: Discussionsupporting
confidence: 83%
“…Adults respond to a similar stimulus with a 255% increase in ýé within 3 min (Bacon, Afifi, Griebel & Camporesi, 1990), whilst lambs respond to a more profound stimulus (8 % Oµ) with a 34-131% increase within 3 min, returning to control values by 8 min (Bureau et al 1986;Côt e et al 1988). The biphasic ýé response during wakefulness is reportedly due to a biphasic VT response (Haddad et al 1982;Laframboise et al 1983;Bonora et al 1984;Bureau et al 1984), or a biphasic VT and f response (Côt e et al 1988). We found that during QS within both postnatal age groups, the biphasic response was due to a biphasic VT and f response (Fig.…”
Section: Saoµ Measurementsmentioning
confidence: 99%
“…The kitten's ventilatory response to acute hypoxia, characterized by rapid and shallow breathing with minimal changes in VE, very closely resembled that previously observed in the same species (5,6,15) and conforms to the breathing pattern response of many other newborn mammals (7). The puppy, on the other hand, responded to 10% O2 with an increase in VT and no changes in f. This species difference could be attributed to the differences in sensitivity to hypoxia (7) as well as differences in the contribution of sleep state to the ventilatory response to hypoxia of newborn dogs and cats (15,16).…”
Section: Ve With No Metabolic Changessupporting
confidence: 78%
“…The puppy, on the other hand, responded to 10% O2 with an increase in VT and no changes in f. This species difference could be attributed to the differences in sensitivity to hypoxia (7) as well as differences in the contribution of sleep state to the ventilatory response to hypoxia of newborn dogs and cats (15,16). The VE-Vc02 ratio was increased in both species during hypoxia; this was previously shown in many newborn species (7), indicating the existence of a hyperventilatory response even in those cases, as in the kittens in our study, in which the absolute value of VE was similar to the normoxic value (7).…”
Section: Ve With No Metabolic Changesmentioning
confidence: 99%
“…This condition is found to be greater in small species and less prominent or possibly absent in adults of larger species [24]. It is observed in newborn animals that hyperventilation during acute hypoxia is mostly achieved by a drop in VO 2 , regardless of the magnitude of the V E response [22,[25][26][27]. In our adult mice, hyperventilation during hypoxia is maintained via a weak hyperpnea and a decreased VO 2 , which is similar with other small species or newborn animals described earlier.…”
Section: Discussionmentioning
confidence: 95%